Events and Processes in Language and Mind - Alexis Wellwood; Angela Xiaoxue He; Haley Farkas (Baltic International Yearbook of Cognition, Logic and Communication, 2019)
Semantic theories predict that the dimension for comparison given a sentence like A gleebed more than B depends on what the verb gleeb means: if gleeb expresses a property of events, the evaluation should proceed by number; if it expresses a property of processes, any of distance, duration, or number should be available. An adequate test of theories like this requires first determining, independently of language, the conditions under which people will understand a novel verb to be true of a series of events or a single ongoing process. We investigate this prior question by studying people’s representation of two cues in simple visual scenes: a) whether some happening is interrupted by temporal pauses, and b) whether and how the speed of an object’s motion changes. We measured representation by probing people’s choice of verb in free-form descriptions of the scenes, and how they segment the scenes for the purposes of counting. We find evidence that both types of cues shape people’s representation of simple motions as events or processes, but in different ways.